Identifikasi Perubahan Karakter Agronomis Padi Transgenik Penanda Aktivasi cv. Asemandi Generasi T1 - Atmitri Sisharmini; Aniversari Apriana; Diah Nurmaliki; Tri Joko Santoso; Kurniawan R. Trijatmiko (Jurnal AgroBiogen, 2013)
The activation-tagged populations of transgenic rice cv.Asemandi have been developed by introducing construct ofactivation taq Ac/Ds into rice genom of cv. Asemandi. The T1transgenic rice populations cv. Asemandi containingconstruct of activation taq have been obtained and neededto be characterized. This study aimed to identify the Bastaherbicide resistant plants, transgenic plants containing hptand bar genes, and changes in agronomic traits. Bastaresistant plant was identified by treating leaf with bastasolution. Hpt and bar genes were detected by PCR usingspecific primers. Phenotype characters were identified byobserving and measuring their agronomic parameters. Thestudy results showed that out of 315 rice transgenic cv.Asemandi T1 treated with Basta solution, 176 (55.87%) plantswere indicated to be resistant to Basta. The results of PCRanalysis revealed that eight rice transgenic cv. Asemanditested contained both hpt and bar genes. In general,compared to the nontransgenic plants, there were changesin several agronomic parameters of T1 transgenic plants cv.Asemandi, including plant height, days to flowering, days toharvesting, periods of grain filling, and weight of 100 grains.Correlation analysis showed that there was no correlationbetween days of harvesting to weight of 100 grains intransgenic rice, but there was correlation in nontransgenicrice. Transgenic rice plants cv. Asemandi with changes inthe agronomic characters will be useful for further study,such as to analyze the function of the genes.